Meningkatkan Kesadaran Keagamaan Dan Pengetahuan Masyarakat Desa Gunung Manaon 1 - Kholidah Nur Ma; Ruly Regar; Juli Annisa; Siti Aminah; Desi Fitriani Hasibuan; Nurhamidah Lbs; Aidina Salsabila; Bayu Setiawan; Rahman Syarif (Jurnal Kabar Masyarakat, 2024)
In overcoming the problems that exist in Gunung Manaon 1 village, various community service methods are needed, one of which is the PAR (Participatory Action Research) method approach. It is hoped that by implementing this based activity, the problem that is the main problem in this research can be resolved. One form of effort to overcome religious problems in the village of Gunung Manaon 1 is by holding an activity to celebrate the Islamic New Year, 1 Muharram 1445 H with the theme "Purifying the Heart in Welcoming the Islamic New Year 1445 H" as a form of participation of the STAIN MADINA KKN group in order to increase public awareness of the importance of celebrating Islamic holidays.